2017
DOI: 10.1073/pnas.1705043114
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of the actin-spectrin–based membrane skeleton in dendrites and soma of neurons

Abstract: Actin, spectrin, and associated molecules form a membraneassociated periodic skeleton (MPS) in neurons. In the MPS, short actin filaments, capped by actin-capping proteins, form ring-like structures that wrap around the circumference of neurites, and these rings are periodically spaced along the neurite by spectrin tetramers, forming a quasi-1D lattice structure. This 1D MPS structure was initially observed in axons and exists extensively in axons, spanning nearly the entire axonal shaft of mature neurons. Suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
162
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(177 citation statements)
references
References 30 publications
15
162
0
Order By: Relevance
“…Similar to the extensively characterized primary hippocampal neurons (D’Este et al, 2015; Ganguly et al, 2015; Han et al, 2017; Xu et al, 2013; Zhong et al, 2014), NSC-derived neurons exhibited a 1D periodic membrane cytoskeleton (Figure S2). …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Similar to the extensively characterized primary hippocampal neurons (D’Este et al, 2015; Ganguly et al, 2015; Han et al, 2017; Xu et al, 2013; Zhong et al, 2014), NSC-derived neurons exhibited a 1D periodic membrane cytoskeleton (Figure S2). …”
Section: Resultsmentioning
confidence: 59%
“…Although initially noted in neuronal axons as adducin-capped actin rings connected by spectrin tetramers to form a periodic, one-dimensional (1D) lattice of well-defined, ~180- to 190-nm periodicity (Xu et al, 2013), related periodic or quasi-periodic cytoskeletal structures have also been observed in dendrites (D’Este et al, 2015; Han et al, 2017) and certain glial cell types (D’Este et al, 2016, 2017; He et al, 2016). Such periodic nanostructures are markedly different from the traditional view of the actin-based cytoskeleton in common mammalian cell types (e.g., dense filament networks and bundles in fibroblasts and epithelial cells) (Chhabra and Higgs, 2007; Pollard and Cooper, 2009; Xu et al, 2012) as well as the spectrin-actin-based cytoskeleton in erythrocytes (2D triangular lattices of short actin filaments connected by spectrin tetramers) (Baines, 2010; Bennett and Baines, 2001; Bennett and Gilligan, 1993; Fowler, 2013; Pan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in contrast to longitudinal and branched actin filaments in the spines, periodic F‐actin structures are very stable and resistant to depolymerization induced by treatment with Latrunculin A and B (Abouelezz, Micinski, Lipponen, & Hotulainen, ). Furthermore, F‐actin forms a membrane‐associated periodic lattice together with βII, βIII, and βIV spectrins, where actin filaments are spaced by spectrin tetramers with a periodicity of approximately 190 nm (Bär et al, ; D'Este et al, ; Han, Zhou, Xia, & Zhuang, ). A very recent correlative dSTORM and electron microscopy study indicated that on an ultrastructural level, this periodically organized F‐actin forms a braid‐like structure containing two long, entwined actin filaments (Vassilopoulos, Gibaud, Jimenez, Caillol, & Leterrier, ).…”
Section: Synaptic Actin Cytoskeletonmentioning
confidence: 99%
“…It has been suggested by Han et al, that spectrin isoforms partially exhibit a compartmentally distinct expression. While βII spectrin seems to be expressed uniformly within axons and dendrites, βIII spectrin is particularly enriched in dendrites (Han et al, ). Indeed, only a fraction of dendritic spines had a periodic lattice formed by F‐actin/βII spectrin (Bär et al, ).…”
Section: Synaptic Actin Cytoskeletonmentioning
confidence: 99%
“…For instance, in addition to crosslinking actin rings to form the periodic membrane structure (MPS) in axon and dendrites, a cytosolic pool of βII‐spectrin independently facilitates bidirectional axonal transport of synaptic vesicles and other cargo (Lorenzo et al, ). Likewise, αII‐spectrin and βIII‐spectrin have been shown to both help assemble the MPS and to associate with motor protein complexes in neurons (Han, Zhou, Xia, & Zhuang, ; Holleran et al, ; Huang et al, ; Lorenzo et al, ; Takeda et al, ).…”
Section: Introductionmentioning
confidence: 99%